Repeated high-intensity exercise in a professional rugby league - Austin, D.; Gabbett, T. J.; Jenkins, D. J. (The Journal of Strength and Conditioning Research, 2011)
The primary aim of this study was to identify and describe the frequency and duration of repeated high-intensity exercise (RHIE) bouts in Australian professional rugby league (National Rugby League) and whether these occurred at critical times during a game. Time motion analysis was used during 5 competition matches; 1 player from 3 positional groups (hit-up forward, adjustable, and outside back) was analyzed in each match. The ranges of RHIE bouts for the 3 positional groups were hit-up forwards 9-17, adjustables 2-8, and outside backs 3-7. Hit-up forwards were involved in a significantly greater number of RHIE bouts (p < 0.05) and had the shortest average recovery (376 ± 205 seconds) between RHIE bouts. The single overall maximum durations of RHIE bouts for the hit-up forwards, the adjustables, and the outside backs were 64, 64, and 49 seconds. For all groups, 70% of the total RHIE bouts occurred within 5 minutes prior of a try being scored. The present data show that the nature of RHIE bouts was specific to playing position and occurred frequently at critical times during the game. These results can be used to develop training programs that mimic the `worst case scenarios` that elite rugby league players are likely to encounter.